Filling ability of ready-to-use or powder-liquid calcium silicate-based sealers after ultrasonic agitation - Tanomaru-Filho, Mário [UNESP]; Lucchesi, Maíra Bonassi [UNESP]; Santos-Junior, Airton Oliveira [UNESP]; Tavares, Karina Ines Medina Carita [UNESP]; Pinto, Jáder Camilo; Guerreiro-Tanomaru, Juliane Maria [UNESP] (FapUNIFESP (SciELO), 2024)
This study evaluated the effect of ultrasonic agitation on the filling capacity of ready-to-use calcium silicate-based sealer Bio-C Sealer (BCS, Angelus, Paraná, Brazil) or powder-liquid BioRoot RCS (BR, Septodont, Saint-Maur-des-Fossés, France) using curved artificial canals by micro-computed tomography (micro-CT). Additionally, flow (mm) and flow area (mm2) were evaluated for both materials. Acrylic resin main canal (60° curvature and 5 mm radius, with 3 lateral canals in the cervical, middle, and apical thirds) were prepared up to size 40/.05 (Prodesign Logic, Brazil). The agitation method was used with ultrasonic tip (US, Irrisonic, Helse, Brazil): BCS, BCS/US, BR, and BR/US. All specimens were filled using the single-cone technique. The samples were scanned by micro-CT (8,74 µm) after obturation. The percentage of filling material and voids were calculated. Flow was evaluated based on ISO 6876/2012 standards (mm) and area (mm2). The data were statistically analyzed using ANOVA and Tukey tests (α = 0.05). BR/US showed lower percentage of filling material in the lateral canals than and, BCS/US (p<0.05). BR/US resulted in a higher percentage of voids than BR in the lateral apical third (p<0.05). BCS showed higher flow than BR (p<0.05). BCS and BR presented proper filling capacity in the simulated curved canals regardless of the use of ultrasonic agitation. However, BR/US showed more voids in the apical third. BCS demonstrates higher filling ability.
Keywords: Endodontics; physical properties; root canal filling; ultrasonic; x-ray microtomography